1989
DOI: 10.1073/pnas.86.23.9588
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal galanin-(1-16) fragment is an agonist at the hippocampal galanin receptor.

Abstract: The galanin N-terminal fragment [galanin-(1-16) The 29-amino-acid-long C-terminal amidated peptide galanin (GAL) (1) has been shown to be widely distributed in the central nervous system of mammals (2-6). GAL-like immunoreactivity has been localized, among other brain regions, in the septal area (4-8) where GAL coexists with acetylcholine in rat (7) and monkey (9) in a subpopulation of cholinergic cell bodies projecting to the hippocampus. and equilibrium binding studies with 1251I-labeled GAL (125I-GAL) have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(53 citation statements)
references
References 30 publications
(90 reference statements)
3
50
0
Order By: Relevance
“…Indeed, the reversal potential of hyperpolarizing responses recorded in ACSF (approximately Ϫ70 mV) did not correspond exactly to values previously determined to characterize K ϩ currents recorded under similar conditions (e.g., Ϫ97 mV) (Bourque, 1988). Moreover, the shift in reversal potential observed on re- Although only one GAL receptor is currently defined by molecular cloning (Habert-Ortoli et al, 1994;Gustafson et al, 1996), various subtypes of GAL receptors are thought to exist in the brain (Fisone et al, 1989;Hedlund et al, 1992Hedlund et al, , 1994Wynick et al, 1993). colleagues (1992, 1994) have characterized a receptor in the brain that has a high affinity for GAL [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] but will not bind GAL .…”
Section: Galanin Inhibits Daps and Phasic Firingmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, the reversal potential of hyperpolarizing responses recorded in ACSF (approximately Ϫ70 mV) did not correspond exactly to values previously determined to characterize K ϩ currents recorded under similar conditions (e.g., Ϫ97 mV) (Bourque, 1988). Moreover, the shift in reversal potential observed on re- Although only one GAL receptor is currently defined by molecular cloning (Habert-Ortoli et al, 1994;Gustafson et al, 1996), various subtypes of GAL receptors are thought to exist in the brain (Fisone et al, 1989;Hedlund et al, 1992Hedlund et al, , 1994Wynick et al, 1993). colleagues (1992, 1994) have characterized a receptor in the brain that has a high affinity for GAL [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] but will not bind GAL .…”
Section: Galanin Inhibits Daps and Phasic Firingmentioning
confidence: 95%
“…In our studies both GAL 1-29 and GAL 1-16 were found to be equipotent in their effects (IC 50 , ϳ10 nM), suggesting that neither of these receptor subtypes is involved in mediating the inhibitory actions of GAL on MNCs. The receptor activated here, however, seems to be similar to that described in the ventral hippocampus (Fisone et al, 1989), which recognizes both GAL 1-29 and the N-terminal fragment GAL [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] .…”
Section: Galanin Inhibits Daps and Phasic Firingmentioning
confidence: 99%
“…The many published structure-activity studies on the effects of galanin fragments and analogues on the GAL-R1 (25)(26)(27)(28)(29)(30)(31) have demonstrated that the active receptor binding part of the peptide resides at the N-terminal portion of the peptide. The presence ofthe unmodified, first two N-terminal amino acid residues is particularly important for retention of high biological potency, since galanin 2-29 and 1-15 are nearly as potent biologically and at receptor displacement as the full 1-29, whereas 3-29, 10-29, and 20-29 are inactive.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological studies with several peptidic agonists and antagonists of galanin receptor suggest the existence of multiple receptor subtypes (7)(8)(9). The first of these receptors (GalR1) has been cloned from several species (10 -13).…”
mentioning
confidence: 99%